Forecasting International Tourist Arrivals in Indonesia Using SARIMA Model - Nurhasanah , Deden; Salsabila , Aurielle Maulidya; Kartikasari, Mujiati Dwi (Enthusiastic : International Journal of Applied Statistics and Data Science, 2022)
Tourism is an important sector that significantly contributes to the economy, so the tourism sector is a priority development program. International tourist arrivals indirectly contribute to the country's economic growth. The government has an important task to increase the number of foreign tourist visits. One way to encourage an increase in foreign tourist arrivals is by forecasting. In general, the time series data for the arrival of foreign tourists has a seasonal pattern. The forecasting method that can model seasonal data is SARIMA. This study aims to predict the arrival of foreign tourists in Indonesia using the SARIMA model. Forecasting results show that the appearance of foreign tourists to Indonesia has increased every period.